Konsumsi dan Konversi Pakan Puyuh (Coturnix coturnix japonica) dengan PenambahanTepung Daun Pepaya (Carica papaya L.) sebagai Pakan Alternatif: Feed Consumption and Conversion of Quail (Coturnix coturnix japonica) with Additional Papaya Leaf Flour (Carica papaya L.) as Alternative Feed - Sukri, Siti Annisa; Novieta, Intan Dwi; Fitriani, (Anoa: Journal of Animal Husbandry, 2022)
The aim of the study was to determine the effect of adding papaya leaf meal (Carica papaya L) to quail feed on consumption and feed conversion as an alternative feed using a completely randomized design (CRD) method with four treatments and three replications. P0: No control treatment 0%. P1: Papaya leaf flour (Carica papaya L) 1% of the amount of feed. P2: Papaya leaf flour (Carica papaya L) 3% of the total feed. P3: Papaya leaf flour (Carica papaya L) 5% of the total feed. The results showed that the addition of leaf flour at different levels had no significant effect (P>0.05) on consumption and feed conversion. Average feed consumption P0 (24.25%), P1 (24.13%), P2 (24.45%), P3 (24.26%), Feed Conversion P0 (2.86%), P1 (2 ,73%) P2 (2.39%) and P3 (2.14%). The best treatment is in the P3 treatment with the addition of 5% papaya leaf flour.